Development of an observation-based tool for ergonomic exposure assessment in informal electronic waste recycling and other unregulated non-repetitive work. (December 2020) - Acquah, Augustine A.; D'Souza, Clive; Martin, Bernard; Arko-Mensah, John; Asabea Nti, Afua; Kwarteng, Lawrencia; Takyi, Sylvia; Botwe, Paul K.; Tettey, Prudence; Dwomoh, Duah; Quakyi, Isabella A.; Robins, Thomas G.; et al.
Most existing ergonomic assessment tools are intended for routine work. Time- and cost- efficient observational tools for ergonomic assessment of unregulated work are lacking. This paper presents the development of an observation-based tool designed to investigate ergonomic exposures among informal electronic waste workers that could be applied to other unregulated jobs/tasks. Real-time coding of observation is used to estimate the relative duration and intensity of exposure to key work postures, forceful exertions, movements, contact stress and vibration. Time spent in manual material handling activities such as carrying, lifting and pushing/pulling of working carts are also estimated. A preliminary study conducted with 6 e-waste workers showed that the tool can easily be used with minimal training and good inter- observer agreement (i.e., 89% to 100%) for most risk factors assessed. This new assessment tool provides effective and flexible options for quantifying ergonomic exposures among workers engaged in unregulated, highly variable work.